Lower Pole Mastopexy-Augmentation: Indications and Applications. (6th February 2020) - Pacifico, Marc D
Abstract: Background: Breast augmentation in primary or secondary patients with long lower pole lengths but appropriately sited nipples is at high risk of "bottoming out" following surgery. The lower pole mastopexy-augmentation (LPMA) was developed to correct long lower pole lengths or preempt bottoming out in breasts deemed at risk, avoiding the requirement for periareolar and vertical breast scar as well as minimizing the requirement for the utilization of synthetic mesh. Objectives: The goal of this short report was to analyze outcomes in patients who underwent the LPMA to determine its application and limitations. Methods: The author reviewed 12 consecutive cases of both primary and secondary situations over a 6-year period. Cases were objectively assessed according to the relationship of the nipple to the point of maximal breast projection on lateral view as well as the upper to lower pole breast proportions. Results: All cases provided good outcomes, with improvements in both the position of the nipple in relation to the point of maximal breast projection and with respect to the upper to lower pole breast ratios. Conclusion: LPMA is a useful addition to the armamentarium in dealing with complex situations in breast augmentation. Level of Evidence: 4: